The prevalence and correlation of cancer-related fatigue and locomotive syndrome in geriatric cancer patients. - Mo-Yu Yang; Ying Chen; Hui Su; Yan Lv; Yu-Ling Yang (PLoS ONE)
Objective To explore the relationship between cancer-related fatigue (CRF) and locomotive syndrome (LS) among Chinese older adults with cancer. Methods This study was a cross-sectional survey. Staged random sampling method was employed to enroll 500 geriatric cancer patients from the Oncology Center of Jiangnan University Hospital in Wuxi, Jiangsu Province, China. Data were collected using General Information Questionnaire, Cancer Fatigue Scale and the Geriatric Locomotive Function Scale. χ2 test, Logistic regression analysis and Spearman analysis were utilized to analyze the data. Results A total of 466 geriatric cancer patients were enrolled in this survey. The occurrence of CRF was 43.8%, and the occurrence of LS was 30.9%. LS were risk factors for the occurrence of CRF in geriatric cancer patients. Advanced old age, fear of falling, comorbid with chronic diseases and CRF were risk factors for LS. CRF was positively associated with LS (r = 0.446, P < 0.001). Conclusion Our findings indicate a potential link between CRF and LS. By addressing LS from various aspects, including controlling the number of complications due to advanced old age and other factors, as well as spreading proper fall-related knowledge and controlling the awareness of fear of falling, healthcare professionals can indirectly alleviate CRF symptoms and improve the overall quality of life for these patients.